American thought and culture in the 21st century - Halliwell, Martin.; Morley, Catherine, 1977- (Edinburgh University Press, 2008)
This ground-breaking book explores the changing patterns of American thought and culture. The 18 essays address such issues as leadership, foreign policy, propaganda, religion, health technology, immigration, 9/11 culture and digital media.